Nutraceutical Value of Kushmanda Avaleha and its Importance for Children’s Health and Growth: A Review Article - Bariha, Mukta; Singh, Sonia; Ghritlahre, Neha; Agrawal, Neeraj; Chauhan, Nagendra Singh; Rathia, Satyawati; Chandravanshi, Lowkesh (Pharmacognosy Reviews)
Nutrition is important factor which is necessary for every age group, According to Ayurveda three pillars of life Ahara (diet), Nidra (sleep), Brahmcharya (celibacy) is called Trayopstambh in life. Body is supported by these three pillars.[1] Ahara is the best of all medicine considered one among these sub pillars, Ahara provide nourishment of the mind, body and soul, Acharya Kashyapa called Ahara as Mahabhaishajya (greatest and best medicine).[2] Karshya in children is a clinical condition the body gets emaciate gradually due to indulgence in rough food and make a person over lean.[3] Kushmanda Avaleha is the best Ayurvedic formulation which provides nourishment, improves appetite and increase the body strength, it is mild formulation that can be used in children. as well as old person.[4] According to Sharangdhara Kushmanda Avaleha is Balya, Vrishya and Brimahana can be used as generalised tonics for the healthy body. Kushmanda Avaleha has been prepared as per the reference given by Acharya Sharangdhara in Sharangdhara Samhita.
Keywords: Ahara; Avaleha; Kushmanda; Nutrition; Undernutrition